Study habits and attitudes of freshmen students of the Bicol Teachers College in relation to academic achievement - Julianda, Lazara Valiente 1927- (s.n.], 1966)
This study determined the study habits and attitudes of the freshman students of the Bicol Teachers College. The sample group and the norm group were compared in terms of study habits and attitudes. The relationship of study habits and attitudes to academic achievement were then identified.